Adjuvant Granulocyte Colony-Stimulating Factor Therapy Results in Improved Spatial Learning and Stimulates Hippocampal Neurogenesis in a Mouse Model of Pneumococcal Meningitis. Issue 1 (January 2015) - Schmidt, Anna Kathrin; Reich, Arno; Falkenburger, Björn; Schulz, Jörg B.; Brandenburg, Lars Ove; Ribes, Sandra; Tauber, Simone C.
<x xml:space="preserve">Abstract</x> Abstract Despite the development of new antibiotic agents, mortality of pneumococcal meningitis remains high. In addition, meningitis results in severe long-term morbidity, most prominently cognitive deficits. Granulocyte colony-stimulating factor (G-CSF) stimulates proliferation and differentiation of hematopoietic progenitor cells and increases the number of circulating neutrophil granulocytes. This study investigated the effect of adjuvant G-CSF treatment on cognitive function after pneumococcal meningitis. C57BL/6 mice were infected by subarachnoid injection of Streptococcus pneumoniae serotype 3 and treated with ceftriaxone and G-CSF subcutaneously or ceftriaxone alone for 5 days. Clinical scores, motor performance, and mortality during bacterial meningitis were unaffected by adjuvant G-CSF treatment. No effect of G-CSF treatment on production of proinflammatory cytokines or activation of microglia or astrocytes was observed. The G-CSF treatment did, however, result in hippocampal neurogenesis and improved spatial learning performance 6 weeks after meningitis. These results suggest that G-CSF might offer a new adjuvant therapeutic approach in bacterial meningitis to reduce long-term cognitive deficits.